2017
DOI: 10.1364/boe.9.000347
|View full text |Cite
|
Sign up to set email alerts
|

Dioptric defocus maps across the visual field for different indoor environments

Abstract: One of the factors proposed to regulate the eye growth is the error signal derived from the defocus in the retina and actually, this might arise from defocus not only in the fovea but the whole visual field. Therefore, myopia could be better predicted by spatio-temporally mapping the 'environmental defocus' over the visual field. At present, no devices are available that could provide this information. A 'Kinect sensor v1' camera (Microsoft Corp.) and a portable eye tracker were used for developing a system fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…330 Recent technological advances also enable accurate monitoring of real-time viewing distances, to allow the dioptric mapping of the visual environment, which helps reveal any potential relationship between chronic viewing distances and myopia development. 329,[331][332][333] Finally, although the preponderance of evidence supports the idea that increased outdoor activities and, by necessity, decreased indoor time, are associated with lower levels of myopia, 320,322 most of these studies can reveal only an association. A number of recent interventional studies have also shown that interventions to increase children's daily outdoor exposure time have resulted in significant reductions in myopia development compared to control groups.…”
Section: Lag Of Accommodationmentioning
confidence: 88%
“…330 Recent technological advances also enable accurate monitoring of real-time viewing distances, to allow the dioptric mapping of the visual environment, which helps reveal any potential relationship between chronic viewing distances and myopia development. 329,[331][332][333] Finally, although the preponderance of evidence supports the idea that increased outdoor activities and, by necessity, decreased indoor time, are associated with lower levels of myopia, 320,322 most of these studies can reveal only an association. A number of recent interventional studies have also shown that interventions to increase children's daily outdoor exposure time have resulted in significant reductions in myopia development compared to control groups.…”
Section: Lag Of Accommodationmentioning
confidence: 88%
“…Certainly, the study brought on some limitations that can restrict its extent, for example, from the recording of the scenarios as already described in the original article[20]. The measurements of peripheral and contact lens profiles may have expanded those limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The dioptric defocus maps from different indoor environments were taken from a previous study by Garcia et al [20], where the information of the relative distance between the gaze point ("accommodative status") and the environmental objects distribution, for a given ±20° around the fovea (total: 40°), were recorded using an RGB-D camera and a head-mounted eye-tracker. For the current work, the maps were flipped upside down and from right to left, in order to match the visual fields between the scenarios and the peripheral refraction.…”
Section: Methodsmentioning
confidence: 99%
“…depths across the visual field) from a scene with a handy device. 28,29 In the current study, it was aimed to quantify the amount of relative scene defocus in a near-work environment, and investigate the relationship between such environments and juvenile refractive development.…”
Section: Introductionmentioning
confidence: 99%